2017
DOI: 10.1049/hve.2017.0120
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy thermoset resins with high pristine thermal conductivity

Abstract: Heat dissipation becomes a critical problem because of the miniaturisation and the increase of power density in electronic devices and electric equipment, which calls for electrical insulating materials with high thermal management capability. Epoxy thermosets have been widely used as electrical insulating materials, but suffer from their low thermal conductivity. This study reviewed the research progress on the development of epoxy thermosets with high pristine thermal conductivity. First, the thermal conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 51 publications
(83 reference statements)
0
46
0
Order By: Relevance
“…A lot of research on space charge suppression by nano-fillers has been carried out [6,7,8,9,10]. And a large number of studies have shown that doping high thermal conductivity fillers can improve thermal conductivity [11,12,13,14]. Most of the research on thermal conductivity focuses on nano-modification of epoxy resins and other polymers.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research on space charge suppression by nano-fillers has been carried out [6,7,8,9,10]. And a large number of studies have shown that doping high thermal conductivity fillers can improve thermal conductivity [11,12,13,14]. Most of the research on thermal conductivity focuses on nano-modification of epoxy resins and other polymers.…”
Section: Introductionmentioning
confidence: 99%
“…39 Significant effort has been devoted to enhancing the thermal conductivity of liquid-crystalline epoxy resins. [9][10][11][12][13]40 These systems are often composed of combinations of liquid-crystalline bisepoxides and common diamines that do not have liquid crystallinity (eg, 4,4′-methylenedianiline (MDA)).…”
Section: Bisepoxide/diamine Systemsmentioning
confidence: 99%
“…At the same time, the insulation material in the equipments work for a long time and the insulation performance could be weakened. [1,2,3] As a result, more attention has been paid to thermal management, which becomes a key issue in many fields. Therefore, the research into the preparation and performance of materials for electrical insulation with high thermal management capabilities is important.…”
Section: Introductionmentioning
confidence: 99%
“…However, most traditional epoxy thermosetting resin materials are amorphous polymers with low thermal conductivity (usually in the range of 0.17-0.21 W/ (mÁK)), which cannot meet the high-power thermal management requirements in a small space. [1,7,8] Adding fillers with high thermal conductivity is an effective way to improve the thermal conductivity of epoxy resin currently, including carbon nanotubes (CNT), graphite, [8][9]10,11] ceramic oxide (Al 2 O 3 , SiO 2 ) [12] and nitride (AlN, BN). [13][14]15,16] Among these materials, Hexagonal BN has been the preferred material used in thermal management applications because of low density, various forms, high mechanical strength, good thermal conductivity (320 W/ (mÁK)) and chemical stability, and inherent electrical insulation.…”
Section: Introductionmentioning
confidence: 99%